Pengembangan Profesional Guru dalam Supervisi Akademik: Sebuah Studi Kualitatif di Madrasah Tsanawiah - Haryanto Haryanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This research aims to examine the implementation, supporting and inhibiting factors, and follow-up actions of the principal’s academic supervision in improving teacher performance. A descriptive qualitative method was used for this study. The research participants included 24 teachers and the school principal, with teachers serving as the main informants. Data were collected through documentation, interviews, and observations. Data analysis was performed using the interactive model of Miles and Huberman, which involves data collection, reduction, display, and conclusion drawing. The findings of the research reveal that: 1) the implementation of academic supervision by the principal involves planning, execution, monitoring, and evaluation based on supervision instruments, which include learning administration tools such as annual programs, semester programs, syllabi, lesson plans, educational calendars, lesson schedules, and a Learning Implementation Plan (RPP); 2) the supporting factors for effective supervision include the availability of school facilities and the teachers’ awareness and preparedness, while the inhibiting factors include the principal's busy schedule and academic background; 3) follow-up supervision is conducted by the teacher coordinator through an assignment letter. The results of this study provide valuable insights into the principal's role in academic supervision and its impact on teacher performance improvement at MTs Mathalibul Huda Jepara.